Prevalence of food addiction among people with diabetes in an urban health center - Hung, Chiun Lau; Leelavathi Muthupalaniappen,; Yogarabindranath Swarna Nantha, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Food Addiction (FA) is a concept of dependence on substance related to the consumption of palatable foods high in fat, sugar, and salt. This dependence may influence dietary modification advice as dietary modification is an essential component in managing people with diabetes. The objective of this study is to determine the prevalence of FA among people with diabetes. A cross-sectional study was conducted between June and August 2021 at Klinik Primer, Pusat Perubatan Universiti Kebangsaan Malaysia (Cheras, Kuala Lumpur) involving 142 people with diabetes. FA was assessed using the validated Bahasa Melayu version of Yale Food Addiction Scale 2.0. The median age of participants was 58 years (IQR=10), and the majority (88%, n=125) of them were above the age of 45 years. A large majority) had central obesity (90.1%, n=128) and were overweight and obese (91%, n=129). The median duration of diabetes was 10 years (IQR=11) with more than two-thirds (63.4%, n=90) of them having diabetes for more than 5 years. Majority (73.9%, n=105) also had poor glucose control with median HbA1c level of 7.5% (IQR =2). Our study found that the prevalence of FA among people with T2DM was low (2.8%, n=4). This could be because the participants were mostly from the older age group with long standing disease. These two features may have influenced their eating behaviour, becoming more compliant and adapted to diabetic diet advice received over the long duration of the condition. A similar study among young diabetics and those with new onset disease may better reflect FA among this group of people.